Dschihad gestern und heute - Ess, Josef van (Walter De Gruyter GmbH Co.KG, 2012)
the third publication in the series of Julius Wellhausen Lecturestreats jihad primarily as a historical phenomenon. Josef van Ess explains the current development not only on the basis of the Koran and the tradition of prophets but also as result of century-long deliberations on how to interpret the term jihad in an adequate manner. Since the present-day Islamic world is also shaped by Western ideas, it seems likely that both Western patterns of action and Islamic modes of thinking are expressed in the current implementation of jihad. Josef van Ess, Universität Tübingen.